2005
DOI: 10.1177/000348940511400308
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss in Lupus Erythematosus Associated with Antiphospholipid Syndrome: Case Report and Review

Abstract: Systemic lupus erythematosus is a disease of unknown cause that manifests with tissue and cellular alterations due to the deposition of antibodies and pathogenic immune complexes. The disease can be associated with anticardiolipin antibody syndrome, a disorder of recurrent vascular thrombosis and thrombocytopenia associated with a persistent anticardiolipin test positivity. In this report, we describe the case of a young woman affected by lupus erythematosus and positive for anticardiolipin antibodies who was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
23
0
1
Order By: Relevance
“…Researchers have also speculated on the existence of a strong relationship between the presence of anticardiolipin antibodies, often found in patients with SLE, and sudden SNHL. 2 27 29 In such cases, the authors argue that the formation of microthrombus in cochlear vessels could be the etiology of sudden SNHL. …”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also speculated on the existence of a strong relationship between the presence of anticardiolipin antibodies, often found in patients with SLE, and sudden SNHL. 2 27 29 In such cases, the authors argue that the formation of microthrombus in cochlear vessels could be the etiology of sudden SNHL. …”
Section: Discussionmentioning
confidence: 99%
“…20 Nevertheless, Compadretti et al 7 reported the case of a patient who received hydroxychloroquine therapy for three years but did not show any signs of cochlear damage.…”
Section: Discussionmentioning
confidence: 99%
“…Apabila vaskulitis terdapat pada arteri labirin dan cabangnya pada penderita LES, keadaan tersebut mengakibatkan gangguan pada pendengaran. [3][4][5] Kerusakan telinga pada pasien LES sudah banyak dilaporkan. Pada penelitian di Polandia pada tahun 2009 terhadap 35 pasien LES, dari pemeriksaan brainstem evoked respons auditory (BERA) didapatkan bahwa 10 orang mengalami gangguan dengar sensorineural secara simetris pada frekuensi tinggi.…”
Section: Pendahuluanunclassified